Comparison of Clinical Practice Guidelines for the Assessment and Management of Cutaneous Melanoma (Literature Review) - Hossein Gandomkar; Monireh Sadat Seyyedsalehi; Kazem Zendehdel; Abolfazl Salari; Mohammad Shirkhoda (Basic & Clinical Cancer Research, 2019)
Evidence shows that there has been an increasing incidence of melanoma cancer in Iran, especially among the young population, which has led to increased mortality,disability and disablement, mostly due to the complications of disease and treatment.New treatments such as targeted therapy are extremely costly, and their results arenot clear. The objective of this study is to review different current guidelines for the management of cutaneous melanoma cancer and discuss the differences in the various phases of patient assessment (prevention, risk factors, genetic assessment, clinical diagnosis,biopsy, staging, treatment and follow-up, pediatric melanoma, melanoma duringpregnancy, and the necessity of social and mental support for melanoma patients). Then, based on the results, we will prepare a national guideline for the management of cutaneous melanoma in accordance with the prevailing conditions in Iran.